Environmental management decision-making in Greek hotels: barriers and drivers to sustainability. (28th February 2022) - Sardianou, Eleni; Gkaragkani, Vaitsa; Kostakis, Ioannis
The present paper addresses the challenges of adopting environmental business practices by hoteliers to put through sustainable entrepreneurship in the tourism sector. The purpose of this research is to study the barriers and the drivers that influence manager's understanding on the decision of adopting environmental management system standards (EMSSs) in their hotels. The importance of these factors on the intention to get an EMS certification is also examined by employing econometric models. The results suggest that a hoteliers' decision to implement corporate environmental practices is being hindered from both external and internal factors. Enhancing corporate image and financing are estimated to be critical motives towards the adoption of formal EMSSs. However, perceived barriers towards obtaining EMS certification differ between environmentally friendly and non-environmentally friendly firms. Managers who have implemented environmental practices consider economic barriers more important than organisational or human-related factors towards adoption of EMSSs.